A tendência literalizante na tradução jurídica juramentada no Brasil : um estudo de caso - Carneiro, Teresa Dias (Language and Law / Linguagem e Direito, 2016)
This article, theoretically grounded on Francis Aubert’s writings, who attempted to shed light on the dierences between strategies and procedures applied to certied translations and free legal translations – stressing a more literalizing trend in the former when compared to the latter –, aims at studying a real case of legal translation, within the sworn translation scope. In conclusion, besides clearly acknowledging in the case under analysis the trend proposed by Aubert, it was deemed signicant to highlight the civil and criminal liabilities imposed upon certied translators by the decree governing the position, in the purpose of providing the study with another explanatory element to the literalizing trend perceived by Aubert.